2014
DOI: 10.2500/ajra.2014.28.4018
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil–Epithelial Cell Interactions Stimulate the Production of MUC5AC Mucin and Profibrotic Cytokines Involved in Airway Tissue Remodeling

Abstract: The results of this study indicate that eosinophil-epithelial cell interactions are important in the pathogenesis of tissue remodeling of eosinophil-predominant airway inflammation such as occurs in nasal polyposis and bronchial asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…28,5760 Glandular hypertrophy and mucous secretion in the airway mucosa are likely to be mediated by the cytokines, tumor necrosis factor (TNF)-α, IL-8 and IL-13. 6163 MUC5AC and MUC5B are the main secreted mucins in the human airway, with MUC5A produced primarily by goblet cells. 64 Viral and bacterial components up-regulate mucin mRNA expression and stimulate mucin secretion in goblet cells.…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…28,5760 Glandular hypertrophy and mucous secretion in the airway mucosa are likely to be mediated by the cytokines, tumor necrosis factor (TNF)-α, IL-8 and IL-13. 6163 MUC5AC and MUC5B are the main secreted mucins in the human airway, with MUC5A produced primarily by goblet cells. 64 Viral and bacterial components up-regulate mucin mRNA expression and stimulate mucin secretion in goblet cells.…”
Section: Pathogenesismentioning
confidence: 99%
“…67,68 Eosinophil-epithelial cell interaction also augments the secretion of MUC5AC, PDGF-AB, VEGF, TGF-β, and IL-8 in culture supernatants. 63 …”
Section: Pathogenesismentioning
confidence: 99%
“…Additionally, as the first line of defense against inhaled antigens, nasal epithelial cells (NECs) play a pivotal role in the pathogenesis of AR. These cells can regulate the degree of the inflammatory reaction in the nasal mucosa by interacting with dendritic cells to induce antigen presentation, by releasing many chemokines to recruit effector cells, and by secreting various growth factors to promote airway remodeling [3][4][5]. Therefore, NECs act as critical initiators and mediators of nasal allergic inflammation and are considered as novel therapeutic targets for the development of anti-allergic medicines.…”
Section: Introductionmentioning
confidence: 98%
“…A separate study in this issue shows that eosinophil-epithelial cell interactions result in proinflammatory cytokine release and tissue remodeling that may contribute to ongoing disease. 2 In addition, Gunel et al 3 have shown that P-glycoprotein is upregulated in eosinophilic CRS, and now they are able to link this to osteitis. 2 Aside from eosinophilic inflammation, further study into T-cells and their function in sinus inflammation continues.…”
mentioning
confidence: 99%
“…2 In addition, Gunel et al 3 have shown that P-glycoprotein is upregulated in eosinophilic CRS, and now they are able to link this to osteitis. 2 Aside from eosinophilic inflammation, further study into T-cells and their function in sinus inflammation continues. T lymphocytes have a known function in the inflammatory process in allergic rhinitis and asthma, and their role in particular CRS subtypes has been a hot topic for recent study.…”
mentioning
confidence: 99%